Peramalan Hasil Panen Jagung di Provinsi Riau menggunakan Metode Single Exponential Smoothing - Safitri, Elfira; Rahma, Adlul Finy; Basriati, Sri (UIN Sultan Syarif Kasim Riau, 2024)
This study discusses the forecasting of corn harvest in Riau Province. One of Indonesia's agricultural food commodities that has potential commodities is corn plants. Corn is one of the world's most important sources of food carbohydrates besides wheat and rice. Data from the Central Statistics Agency (BPS) of Riau Province in 2020, corn production was 30,884 tons. This figure is much more than in 2021 where the production only reached 17,218 tons. Due to the decline in production, it is necessary to forecast production results for 2024. The purpose of the study is to find out the prediction of the number of corn harvests in 2024. The method used in this study is the Single Exponential Smoothing Method. Based on the results of the study, the total corn harvest in 2024 was 8,511.33 tons and MAPE was 0.58% with α = 0.9.